A Comparative Experimental and Computational Study of Heterometallic Fe‐M (M = Cu, Ag, Au) Carbonyl Clusters Containing N‐Heterocyclic Carbene Ligands. Issue 22 (11th May 2020) - Berti, Beatrice; Bortoluzzi, Marco; Cesari, Cristiana; Femoni, Cristina; Iapalucci, Maria Carmela; Mazzoni, Rita; Zacchini, Stefano
Abstract : The [Fe(CO)4 M(NHC)] – (M = Cu, NHC = IMes, 1 ; M = Cu, NHC = IPr, 2 ; M = Ag, NHC = IMes, 3 ; M = Ag, NHC = IPr, 4 ; IMes = C3 N2 H2 (C6 H2 Me3 )2 ; IPr = C3 N2 H2 (C6 H3 i Pr2 )2 ) mono‐anions were obtained from the reaction of Na2 [Fe(CO)4 ]· 2thf with one equivalent of M(NHC)Cl (M = Cu, Ag; NHC = IMes, IPr) in dmso. Furthermore, the reaction of Na2 [Fe(CO)4 ]· 2thf with two equivalents of M(NHC)Cl in thf afforded the neutral compounds Fe(CO)4 M(NHC)2 (M = Cu, NHC = IMes, 11 ; M = Cu, NHC = IPr, 12 ; M = Ag, NHC = IMes, 13 ; M = Ag, NHC = IPr, 14 ). 2 and 4 further reacted with one equivalent of M(IPr)Cl (M = Cu, Ag, Au) resulting in the trimetallic clusters Fe(CO)4 Cu(IPr)Ag(IPr) (18 ), Fe(CO)4 Cu(IPr)Au(IPr) (19 ), and Fe(CO)4 Ag(IPr)Au(IPr) (20 ). 1–4, 11–14 and 18–20 have been spectroscopically characterized by IR, 1 H and 13 C 1 H NMR techniques. The molecular structures of 2, 12, 18, 19 and 20 have been determined through single‐crystal X‐ray diffraction. The structure, bonding and stability of the copper and silver IMes derivatives were compared to the related Fe‐Au clusters previously reported on the basis of theoretical calculations. Stability of the Fe–M bonds decreases in the order Au > Cu > Ag, and the same trend was found for what concerns the M‐IMes interactions. The decomposition products of 1–4, 11–14 and 18–20 have been studied allowing, among the others, the structural characterization of the new species [Fe2 (CO)8 Ag(IPr)] – (10 ) and Fe(CO)4 (CH2 IMes) (21 ). Abstract : The stability of heterometallic carbonyl clusters containing NHC ligands decreases in the order Au > Cu > Ag as evidenced by experimental and computational studies.